Design and Fabrication of Microfluidic Biochips for Early Detection of Sexually Transmitted Diseases - Khalil Zaman; Omar Khan; Jamil Khan (Journal of Biomedical and Techno Nanomaterials, 2024)
Sexually transmitted diseases (STDs) remain a global health problem that requires early detection and rapid treatment. This study aims to design and fabricate microfluidic biochips for the early detection of several PMS-causing pathogens, such as Chlamydia trachomatis, Neisseria gonorrhoeae, and Trichomonas vaginalis. This research method involves designing chips with microfluidic technology, fabrication using lithography techniques, and testing the sensitivity and specificity of blood, urine, and cervical fluid samples. The results show that the biochip developed has a sensitivity of up to 92% and a specificity of 95%, with a detection time of less than 10 minutes. The biochip is also capable of detecting a variety of pathogens in a single device, making it an efficient diagnostic tool. In conclusion, this microfluidic biochip has the potential to be a fast, cheap, and effective PMS detection tool for use in the field. Further research needs to be conducted to test the sustainability of chip performance under real-world conditions and for further development in the detection of various other pathogens.